Age and growth rate determination from pectoral and dorsal fin region scales of a hillstream teleost Barilius bendelisis (Ham.) with a note on difference in their structure - Rawat, V S; Nautiyal, Prakash (Indian Journal of Fisheries, 2011)
The scales from dorsal (DFR) and pectoral fin regions (PFR) of Barilius bendelisis were studied for sculptural details and their suitability for use in age and growth determination. The scales of DFR and PFR did not indicate significant difference in the structural details, but slightly differed in terms of width, number of circuli, radii and circuli in terminal zone. The growth rates obtained from DFR-s (11.26 ±5.2mm) and PFR-s (9.98±2.3mm) when 1st and 2nd growth rings were laid, do not seem to differ much apparently. The average growth characteristics (Cth-10.43 ±2.25), growth constant (Clt-0.21414 ±0.0568), spec fie rate of linear growth (Cl-12.94 ±3.6 mm) and specific rate of weight increase (Cw-33.35 ±8.57 g) were also computed.